2020
DOI: 10.24940/theijhss/2020/v8/i2/hs2002-001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Ghana School Feeding Programme on School Enrolment, Retention and Attendance in the Atwima Nwabiagya Municipal in the Ashanti Region of Ghana

Abstract: Education is recognized universally as a basic human right (Adekunle & Ogbogu, 2016). The article 26 of the Universal Declaration of Human Rights of 1948 declared that everyone has the right to education. Elementary education under the article is required to be compulsory and free to all regardless of religion, gender, status or ethnic background. The education of the citizenry is crucial to the socioeconomic development of individuals and the whole nation (Braimah & Oduro-Ofori, 2005). It is a crucial process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The benefits of fund on beneficiaries' livelihood as evidenced in this paper is further consistent with Agyemang [25], and Edusei and colleagues [29]. We also found beneficiaries felt their sense of dignity was enhanced as a result of engaging in a livelihood generation activity and felt valued in their family and community life.…”
Section: Plos Onesupporting
confidence: 89%
See 3 more Smart Citations
“…The benefits of fund on beneficiaries' livelihood as evidenced in this paper is further consistent with Agyemang [25], and Edusei and colleagues [29]. We also found beneficiaries felt their sense of dignity was enhanced as a result of engaging in a livelihood generation activity and felt valued in their family and community life.…”
Section: Plos Onesupporting
confidence: 89%
“…Fund recipients used funds to set up businesses or expanded existing ones, in addition to health and educational needs. Agyemang [25] further found 71% respondents indicating the Fund was useful for their livelihoods.…”
Section: Previous Research On the Disability Fundmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar qualitative study in Ghana confirmed that teachers, caterers, parents and school administrators agreed with the fact that SFP had an impact on enrolment, attendance, completion and the academic performances of primary schoolchildren, in addition to cognitive development and the reduction of hunger ( 48 ) .…”
Section: Discussionmentioning
confidence: 71%